DIGITAL TWIN CONCEPT FOR INDONESIA DIGITAL GOVERNMENT INFORMATION TECHNOLOGY GOVERNANCE - Hari Setiabudi Husni; Ford Lumban Gaol; Suhono Harso Supangkat; Benny Ranti (Asosiasi Dosen Muda Indonesia, 2022)
This paper explores the possibility of digital twin concept implementation framework in Indonesia Digital Government Systems (IDGS) using Information Technology (IT) Governance indicators states in Indonesian Government regulation. The concept of Indonesia Digital Government regulated by Indonesia Presidential Regulation no. 95 year 2018 that define digital government as a governance that adapting to advances of technology information and communication and utilize optimally so it can provide service to citizen in most efficient and effective way. Indonesia government implement IT Governance using regulation publish by the Minister of State Apparatus and Bureaucracy Reform No. 59 year 2020 about monitoring and evaluation of Indonesia Digital Government System. In the regulation, the governance consists of monitoring, which is a systematic assessment process through verification of information on the results of the Self-Assessment to measure the maturity level of implementation and the evaluation, is a process of self-assessment systematically through verification and clarification of information which can be continued with information validation to the results of the Self-Assessment to measure maturity level of digital government system implementation. The concept of exploiting digital twin concept to Governed IT Management is a framework introduce by Geert Poels, Henderik A. Proper and Dominik Bork in 2021. The Digital Twin concept itself already utilize to do such as monitoring data, data analysis, conduct simulation, and enhances performance of assets. The framework will be use as a technology infrastructure reference model that facilitate Digital Twin in conceptual aspect where process of IT governance, organizational IT assets management and IT management processes, connected.